2011
DOI: 10.1038/onc.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

Annexin-1 interacts with NEMO and RIP1 to constitutively activate IKK complex and NF-κB: implication in breast cancer metastasis

Abstract: The molecular mechanisms underlying constitutive nuclear factor-jB (NF-jB) activation in solid tumors has not been elucidated. We show that Annexin-1 (ANXA1) is involved in this process, and suppression of ANXA1 in highly metastatic breast cancer cells impedes migration and metastasis capabilities in vitro and in vivo. ANXA1 expression correlates with NF-jB activity, suggesting that ANXA1 may be required for the constitutive activity of IjB kinase (IKK) and NF-jB in highly metatstatic breast cancer. Gel-filtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
116
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 37 publications
5
116
0
Order By: Relevance
“…Down-regulation of ANXA1 has also been shown in carcinogenic models to inhibit cell migration/invasion (15,48), suggesting that ANXA1 could possibly be pro-migratory in carcinogenesis. Recent studies from our lab and others have demonstrated that ANXA1 is indeed pro-migratory in cancer cells, whereas silencing ANXA1 reduces metastatic capability (15). Altogether, cell motility plays a central part in coordinating normal physiological and pathological processes including wound healing and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Down-regulation of ANXA1 has also been shown in carcinogenic models to inhibit cell migration/invasion (15,48), suggesting that ANXA1 could possibly be pro-migratory in carcinogenesis. Recent studies from our lab and others have demonstrated that ANXA1 is indeed pro-migratory in cancer cells, whereas silencing ANXA1 reduces metastatic capability (15). Altogether, cell motility plays a central part in coordinating normal physiological and pathological processes including wound healing and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms proposed in this adhesion inhibition is the down- regulation and shedding of a cell adhesion molecule L-selectin on the leukocytes (46,47). Down-regulation of ANXA1 has also been shown in carcinogenic models to inhibit cell migration/invasion (15,48), suggesting that ANXA1 could possibly be pro-migratory in carcinogenesis. Recent studies from our lab and others have demonstrated that ANXA1 is indeed pro-migratory in cancer cells, whereas silencing ANXA1 reduces metastatic capability (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present findings on ANXA1 as a regulator of the TRIF pathway by binding to TRIF and TBK1 provides a mechanistic basis linking GC and TRIF pathway through ANXA1. We have previously reported that ANXA1 can bind to NEMO and RIP1 (40) to enhance the activation of NF-kB. It is possible that the same regions of ANXA1 bind to TBK1 as well to regulate IRF3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The gene products of ADRB1, RIPK1 belong to the gap junction signaling, which is important for cell motility. [29][30][31] STMN1, which has a role in cell migration, was reported to be upregulated by mutp53. 32 It is possible that some of these genes mediate the promoting effect of Pontin on mutp53 GOF.…”
mentioning
confidence: 99%